Объяснение:
-x³+675x-(15+x)(225-15x+x²)>0
-x³+675x-(3375+x³)>0
-2x³+675x-3375>0
-2x³+450x+225x-3375>0
-2x³+30x²-30x²+450x+225(x-15)>0
-2x²(x-15)-30x(x-15)+225(x-15)>0
(x-15)(-2x²-30x+225)>0
Допустим:
x-15=0; x₁=15
Проверка при x₁<15:
-0³+675·0-(15+0)(225-15·0+0²)>0
-15·225>0; -3375<0 - неравенство не соблюдается.
Допустим:
-2x²-30x+225=0
2x²+30x-225=0; D=900+1800=2700
x₂=(-30-√2700)/4=(-30-30√3)/4=(-15√3 -15)/2
x₃=(-30+√2700)/4=(15√3 -15)/2
Проверка при x₂>(-15√3 -15)/2:
-0³+675·0-(15+0)(225-15·0+0²)>0; -3375<0 - неравенство не соблюдается.
Проверка при x₃>(15√3 -15)/2:
-10³+675·10-(15+10)(225-15·10+10²)>0
-1000+6750-25·(225-150+100)>0
5750-25·175>0; 5750-4375>0; 1375>0 - неравенство соблюдается.
Следовательно, (-∞<x<(-15√3 -15)/2)∨((15√3 -15)/2<x<15).
ответ: x∈(-∞; (-15√3 -15)/2)∪((15√3 -15)/2; 15).
Объяснение:
2.
а) ву²–вх²= в(у²–х²)= в(у–х)(у+х)
б)–у²–10у–25= –(у+5)²= –(у+5)(у+5)
в)с⁴а²–а⁴с²= а²с²(с²–а²)=а²с²(с–а)(с+а)
г)х–225х³= х(1–225х²)= х(1–15х)(1+15х)
д) 8а²–16ав+8в²= 2(4а²–8ав+4в²)= 2(2а–2в)(2а–2в)
е)64–х⁴= (8–х²)(8+х²)
ж)–6х²+36х–54= –6(х²–6х+9)= –6(х–3)(х–3)
з) 147а³–3ав²= 3а(49а²–в²)= 3а(7а–в)(7а+в)
3.
а) у²(2+у)=у(у–1)(у+3)
2у²+у³= (у²–у)(у+3)
2у²+у³=у³+3у²–у²–3у
–3у=0
у=0
б)4+4а–а²–а³=0
4(1+а)–а²(1+а)=0
(4–а²)(1+а)=0
совокупность:
4–а²=0
1+а=0
совокупность:
а=2
а=–1
в)16а²+9–24а=0
16а²–24а+9=0
(4а–3)(4а–3)=0
а=–0,75
Вроде как, особо не уверена